The Effect of Competency and Infrastructure on Public Contentment Through Service Caliber at The UPTD BLK of West Tanjung Jabung District - Dewi Sartika; M. Zahari; Fakhrul Rozi Yamali (Dinasti International Journal of Digital Business Management, 2026)
This study intends to investigate the influence of expertise and infrastructure on public contentment through service caliber at the Technical Implementation Unit (UPTD) of the West Tanjung Jabung Regency Vocational Training Center (BLK). This study on the payroll a descriptive and quantitative technique with a survey method. The study population comprised all 106 users of vocational training services at the UPTD BLK in West Tanjung Jabung Regency, and the total population was sampled (census technique).  Data were obtained by a questionnaire utilizing a Likert scale and analyzed using route analysis derived from Partial Least Squares (PLS). The results demonstrated that expertise and infrastructure had a favorable and meaningful effect on service caliber.  Furthermore, service caliber had a favorable and meaningful effect on public contentment.  The path analysis also indicated that service caliber mitigated the influence of expertise and infrastructure on public contentment. This study gives practical insights for the UPTD BLK in West Tanjung Jabung Regency to improve personnel competency and the supply of facilities and infrastructure to achieve optimal service caliber and boost public contentment